Strengthening Local Government Capacity in Central Lombok Regency, Indonesia - Mujahidin (Yayasan Hisnul Muslim Lombok, 2025)
Public service innovation has become an important strategy for improving government performance and enhancing service quality in the era of decentralization and digital governance. Local governments are increasingly required to develop innovative approaches to respond to growing public demands for efficient, transparent, and accessible services. This study aims to analyze the implementation of public service innovation in Central Lombok Regency, Indonesia, particularly in improving the effectiveness and accessibility of government services. The research employs a qualitative case study approach to explore the dynamics of innovation within local public service institutions. Data were collected through in-depth interviews with government officials, analysis of policy documents, and observation of service practices in relevant public service agencies. The findings reveal that public service innovation in Central Lombok is primarily manifested through administrative simplification, integrated service delivery through the One-Stop Integrated Service Office (DPMPTSP), and the adoption of digital service platforms. These innovations have contributed to improving service efficiency, reducing bureaucratic complexity, and increasing transparency in service delivery. However, the study also identifies several challenges, including limited digital infrastructure, uneven digital literacy among citizens, and constraints in human resource capacity within local government institutions. These limitations affect the sustainability and scalability of innovation initiatives. The study concludes that strengthening institutional capacity, technological infrastructure, and collaborative governance is essential to ensure the sustainability of public service innovation. The findings contribute to the broader literature on public sector innovation, particularly in the context of decentralized governance in developing countries.